Analysis of the needs of teachers and students on the inquiry-flipped classroom model in chemistry lessons - Suci Desmarani; Muhammad Rusdi; Haryanto Haryanto; Sugeng Triwahyudi (Pascasarjana Universitas Negeri Medan, 2022)
This study was conducted with the aim of looking at how the general description of student characteristics, material analysis, infrastructure, and problems in chemistry learning were used to support research on the use of inquiry based - flipped classroom E-LKPD in order to maximize the teacher's efforts to improve creative and self -thinking skills student efficacy. This research is a quantitative descriptive analysis research. data collection using interview and observation techniques. Interviews were conducted with teachers of chemistry subjects. The sample of students was taken by random sampling. The research subjects were 47 state high school students in Jambi City. The results showed that 78.7% of students had difficulty understanding chemistry lessons, and 61.7% of students had difficulty understanding chemical concepts, and 51.1% of students had difficulty understanding chemistry questions. The results of the study also said that 97.9% of students needed learning multimedia (e-LKPD). Based on the results of the study, it can be concluded that the inquiry-flipped Classroom model assisted by e-LKPD can be used as a solution to meet the needs of students and teachers, because this learning model is oriented towards student activity and uses technology in the learning process.Keywords:Chemical bond, Flipped classroom, Inquiry, Self efficacy, 21st century learning